STRATEGI PENGEMBANGAN INDUSTRI KEBAB FROZEN DI ERA PANDEMI COVID-19 DI KOTA PEKANBARU - Sundari Ramadani M; Jahrizal; Mardiana (Juremi: Jurnal Riset Ekonomi, 2021)
This study aims to analyze the development of the frozen kebab industry in Pekanbaru City. In this study, the number of research population is all frozen kebab industry business actors in Pekanbaru City, namely 7 businesses, the sampling in this study uses the census method because the population is less than 100 so that the entire population is sampled. The analytical method used is descriptive quantitative. Measurements carried out in this study are by using a questionnaire, the existing data is processed and analyzed using data tabulation, while to analyze it is by using a SWOT analysis tool. Based on the results of the study, it is known that the results of the IE matrix analysis are compiled by plotting the total score of the IFAS and EFAS matrices. On the average weight and rating, these internal factors have the highest average weight and rating. Weakness is frozen resistance outside of refrigeration. This means that respondents consider this factor to be the most important weakness compared to other weaknesses. The main opportunity for the frozen kebab industry in Pekanbaru City is the increasing use of social media which is increasingly becoming an easier and more economical promotion target. While the threat is the existence of policies that require social distancing so as to limit direct meetings with consumers. This means that respondents consider this factor to be the most important threat compared to other threat indicators. Based on the IE Matrix, it is in the S-O strategy column, this is because the meeting between IFAS and EFAS is on opportunities and strengths.